Examining How Financial Literacy Moderates the Factors Affecting Investment Decision in Capital Market - Afitra Azzahra; Ira Wikartika (Amkop Management Accounting Review (AMAR), 2026)
The shifting global economic landscape has heightened public awareness regarding the importance of effective financial management as a means to achieve financial independence. Investment is one strategy employed to reach this objective. However, In reality, personal investment choices are often shaped by psychological influences, which can result in irrational investment behavior. This exploration seeks to observe how experienced regret, risk tolerance, and influencers affect investment decisions in the capital market among Generation Z investors in Surabaya City, while considering financial literacy as a moderating factor. This search employed a quantitative approach, gathering the primary data through questionnaires that distributed to 160 respondents. The sample was chosen using purposive sampling, and the data analysis was conducted using the SEM-PLS method supported by SmartPLS software. The study findings indicate that experienced regret and risk tolerance contribute to investment decisions, whereas influencers do not. Financial literacy was proven to significantly moderate the correlation between experienced regret, risk tolerance, and influencers on investment decision.